Pisuke Accounting in the Wedding Culture of the Sasak Tribe in Central Lombok - Mohamad Dirjan; M. Ali Fikri (International Journal of Economics, Business and Innovation Research, 2025)
This research discusses the pisuke tradition in Sasak traditional marriages in Central Lombok Regency. Pisuke is an important part of Sasak marriage culture, in the form of giving a sum of money by the groom to the bride's family as a symbol of appreciation for the family's efforts to raise and educate their daughter. This study uses a qualitative method with an ethnographic approach to analyze the factors that influence the value of pisuke, especially the bride's education level. The research findings show that the higher the education of the woman, the greater the pisuke value requested, reflecting education as an important investment in Sasak culture. The value of pisuke reflects not only economic dimensions but also social and gender aspects, which strengthen inter-family relationships and women's position in society. With an accounting approach, pisuke can be seen as a form of transaction that includes social, cultural and economic values. This research provides a new perspective in understanding cultural traditions in a modern economic context.